Tailoring business models for small-medium food enterprises in Eastern Africa can drive the commercialization and utilization of vitamin A rich orange-fleshed sweet potato puree - Annette, N.M.; Makeda, T.; Mukani, M.; Muzhingi, T. (Walter de Gruyter GmbH, 2023)
Orange-fleshed sweet potato (OFSP), a promising crop for alleviating vitamin A deficiency (VAD), can be utilized at home and in commercial food processing as a basic and functional ingredient. The root can be processed into puree that is incorporated in baked and fried products and other products, with a high acceptability rate. When used as a wheat substitute in a bakery, the OFSP puree significantly cuts the production cost. In the last few years and with the intensified promotion of OFSP and OFSP puree products as a sustainable food-based strategy to tackling VAD at the population level, many small-medium food enterprises (SMEs) in the Eastern Africa Region (EAR) have shown great interest in utilizing the OFSP puree in their commercial product lines. However, the OFSP and OFSP puree value chain for commercial usage is still underdeveloped poising raw material supply challenges. In addition, the SMEs are early-stage businesses lacking the capacity and proper business models to propel them to sustainably venture into OFSP processing. As such, there is a need to engage and support SMEs in tailoring business models suitable for their scaling needs along the OFSP value chain to make available in the market, affordable nutrient-dense OFSP-puree products. This article presents the approach that was used to offer tailored Business Development Services (BDS) for selected SMEs in EAR to scale up their capacity to commercialize OFSP puree and puree-based products. The BDS designed and supported six integrated modules: business profile development, business model canvas, understanding the numbers/finances, OFSP value chain analysis, SWOT analysis, and growth plan, to develop and document individual business capacities and aspirations. The SMEs identified numerous opportunities and entry points for OFSP value chain development and expansion through the BDS depending on their business needs.